The End is not yet: Standing firm in apocalyptic times - Huggins, Jonathan (Stellenbosch Theological Journal, 2018)
The End is not yet: Standing firm in apocalyptic timesby De Gruchy, John W. 2017, Minneapolis: Fortress Press. ISBN 9781506431574